Global agri‐food chains in times of COVID‐19: The state, agribusiness, and agroecology in Argentina. (25th May 2021) - Gras, Carla; Hernández, Valeria
Abstract: The issues posed by the unfolding impacts of COVID‐19 are very uneven in the case of Argentina, a major global commodity exporter. As domestic food prices have continued to rise, worsening the living conditions of millions, and state policies seek to guarantee the population's access to food, the hegemonic agribusiness sector is fostering new alliances to strengthen its integration into global agri‐food markets. A full understanding of agribusiness' strategies needs to address the changes brought about by the pandemic on peasant‐like farmers and rural workers, the alternatives they have developed (mainly agroecology) in their struggle against the dominant food regime in recent years, and explore the extent to which local expressions of this antagonism are being reshaped. In doing so, we also pay attention to the role of the state.